Răspuns :
[tex]3 \frac{5}{18} - 2 \frac{1}{9} = \frac{59}{18} - \frac{19}{9} = \frac{59 - 38}{18} = { \frac{21}{18} }^{3} = \frac{7}{6} [/tex]
[tex]7 \frac{11}{15} - 2 \frac{1}{5} = \frac{77}{15} - \frac{2}{5} = \frac{77 - 6}{15} = \frac{71}{15} = 4 \frac{11}{15} [/tex]
F)3×18+5/18-2×9+1/9
54+5/18-18+1/19
59/18-19/19=189/162
G)7×15+11/15-2×5+1/5
165+11/15-10+1/5
.............................
35.2/75-165/75=-129,8/75
54+5/18-18+1/19
59/18-19/19=189/162
G)7×15+11/15-2×5+1/5
165+11/15-10+1/5
.............................
35.2/75-165/75=-129,8/75